THE INFLUENCE OF MEDIA ON THE PROMOTION OF SMK PGRI 1 TANGERANG - Kurnaedi, Didi; Gumiwa, Aep (STIT AL MULTAZAM, 2023)
The purpose of this research is to find out and describe the contribution of the media used on students' decisions to choose SMK as their secondary school. For some schools, especially private schools, the role of promotion is very beneficial because with promotion they are able to attract more students. However, in promotion it is also necessary to have good media to attract or invite people to want to use or use the products/services they offer. It is for schools, especially private schools, to make advertising media as attractive as possible as well as informative and persuasive so that students feel interested in choosing the school concerned as their next school. This research uses a descriptive quantitative method to find out how much the advertising media contributes to students' decisions to choose SMK as their secondary school. Data were obtained from PGRI 1 Tangerang Vocational School, primary data collection was carried out by distributing questionnaires to 155 students as a sample of 266 class X students. The validity of the data was obtained by testing the validity and reliability as well as by the participation of researchers and observation diligence. The results of the study revealed that the advertising media used by SMK PGRI 1 Tangerang such as banners, brochures, posters, stickers, etc. were able to contribute quite a lot to students' decisions to choose SMK PGRI 1 Tangerang as a secondary school. Advertising media is able to help students make decisions about choosing SMK PGRI 1 Tangerang as their secondary school, while the rest is contributed by other factors. Although the advertising media used by SMK PGRI 1 Tangerang has been able to contribute quite a lot to students' decisions choosing SMK PGRI 1 Tangerang as their secondary school, it is better if SMK PGRI 1 Tangerang maximizes the use of existing media and increases PPDB in carrying out promotions so that it is more many prospective students feel interested in making SMK PGRI 1 Tangerang their secondary school.